Disseminated Peritoneal Leiomyomatosis: A Rare Case Report in a Woman without a Prior History of Uterine Leiomyomas - Lameiras Costa, MD (2022)
Disseminated peritoneal leiomyomatosis (DPL) is a rare disease characterized by multiple leiomyomas disseminated throughout the peritoneal cavity, occurring most commonly in women of childbearing age. Although typically benign, DPL may degenerate into malignancy. As the majority are asymptomatic, these tumors are usually incidentally found incidentally. Differential diagnosis includes peritoneal carcinomatosis peritoneal or abdominal disseminated malignancy; the clinical and radiological context can help differentiate these entities, but only histopathological examination achieves the final diagnosis. The authors present a case of a woman with DPL found during infertility workup. She had undergone laparoscopic broad ligament myomectomy 5 years previously, but there was no prior history of uterine leiomyomas. A revision of the clinical, pathological and imaging features of this entity was also performed.